Interleukin-4-Mediated Oxidative Stress Is Harmful to Hippocampal Neurons of Prothrombin Kringle-2-Lesioned Rat In Vivo - Chung, Young Cheul (Antioxidants (Basel), 2020)
The present study investigated the effects of reactive microglia/macrophages-derived interleukin-4 (IL-4) on hippocampal neurons in prothrombin kringle-2 (pKr-2)-lesioned rats. pKr-2 was unilaterally injected into hippocampus in the absence or presence of IL-4 neutralizing antibody (IL-4Nab). Immunohistochemical analysis showed a significant loss of Nissl(+) and NeuN(+) cells and activation of microglia/macrophages (increase in reactive OX-42(+) and OX-6(+) cells) in the hippocampus at 7 days after pKr-2 injection. The levels of IL-4 expression were upregulated in the reactive OX-42(+) microglia/macrophages as early as 1 day, maximal at 3 days and maintained up to 7 days after pKr-2 injection. Treatment with IL-4Nab significantly increased neuronal survival in pKr-2-treated CA1 layer of hippocampus in vivo. Accompanying neuroprotection, IL-4 neutralization inhibited activation of microglia/macrophages, reactive oxygen species-derived oxidative damages, production of myeloperoxidase- and inducible nitric oxide synthase-derived reactive nitrogen species and nitrosative damages as analyzed by immunohistochemistry and hydroethidine histochemistry. These results suggest that endogenous IL-4 expressed on reactive microglia/macrophages mediates oxidative/nitrosative stress and play a critical role on neurodegeneration of hippocampal CA1 layer in vivo.